2018
DOI: 10.1016/j.jgr.2018.07.004
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study on immune-stimulatory and antioxidant activities of various types of ginseng extracts in murine and rodent models

Abstract: BackgroundGinseng (Panax ginseng) is a widely used traditional herbal supplement that possesses various health-enhancing efficacies. Various ginseng products are available in market, especially in the Korean peninsula, in the form of drinks, tablets, and capsules. The different ginseng types include the traditional red ginseng extract (RGE), white ginseng, and black red ginseng extract (BRGE). Their fermented and enzyme-treated products are also available. Different treatment regimens alter the bioavailability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 39 publications
(39 reference statements)
0
21
0
1
Order By: Relevance
“…Acetaminophen (APAP), a widely antipyretic-analgesic agent, is known to be safe for medical purpose, but it can also damage the liver when taken in excess, to acute liver failure and death [ 18 ]. In a study by Saba et al, when 500 mg/kg KRG were administered to rats with oxidative stress with APAP for 7 days, the liver SOD, CAT and GPx activities were increased in the KRG group, while the levels of 8-hydroxy-2′-deoxyguanosine, AST, and LDH were decreased [ 19 ]. In addition, Seong et al reported that when acute liver failure was triggered by APAP, the SOD and CAT activities were increased, with the decreased lipid peroxide content in KRG group [ 20 ].…”
Section: Evaluation Of Krg Efficacy In Animal Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Acetaminophen (APAP), a widely antipyretic-analgesic agent, is known to be safe for medical purpose, but it can also damage the liver when taken in excess, to acute liver failure and death [ 18 ]. In a study by Saba et al, when 500 mg/kg KRG were administered to rats with oxidative stress with APAP for 7 days, the liver SOD, CAT and GPx activities were increased in the KRG group, while the levels of 8-hydroxy-2′-deoxyguanosine, AST, and LDH were decreased [ 19 ]. In addition, Seong et al reported that when acute liver failure was triggered by APAP, the SOD and CAT activities were increased, with the decreased lipid peroxide content in KRG group [ 20 ].…”
Section: Evaluation Of Krg Efficacy In Animal Studymentioning
confidence: 99%
“… Subject type State Main Antioxidant effects of KRG Type of Ginseng Ref. Animal ( in vivo ) Normal lipid peroxidation↓, oxygen free radical↓, CAT↑, GPx↑ G-Rb1 and G-Rg1 [ 7 ] lipid peroxidation↓, oxygen radical scavenging activity↑, MDA↓, CAT↑, GPx↑ G-Rb1 and G-Rg1 [ 8 ] Lipid peroxidation↓, DPPH radical scavenging activity↓ ginsenosides [ 9 ] MDA↓, SOD↓, CAT↓, GR↑ total saponin [ 10 ] SOD↑, H 2 O 2 ↑, CAT↑, MDA↓ red ginseng [ 11 ] Liver disease oxygen radical scavenging activity↑ Korean red ginseng [ 14 ] ALT↓, AST↓, ALP↓, urea↓, creatinine↓, uric acid↓, glucose↓, NO↓ ginseng [ 15 ] lipid peroxidation↓ Korean ginseng [ 16 ] ALT↓, AST↓, SDH↓, γ-GT↓, ALP↓, LDH↓, CYT P 450 ↓ Korean red ginseng [ 17 ] SOD↑, CAT↑, GPx↑, serum 8-hydroxy-20-deoxyguanosine↓, AST↓, LDH↓ ginseng extracts [ 19 ] SOD↑, CAT↑, lipid peroxidation↓ white and red ginseng extracts [ 20 ] ALT↓, AST↓, MDA↓, SOD↑, CAT↑, GPx↑ Korean red ginseng [ 21 ] ALT↓, AST↓, ALP↓, MDA↓, SOD↑, CAT↑, GPx↑ Panax ginseng [ 22 ] lipid peroxidation↓, GSH↑, GST↑, GPx↑ Korean red ginseng [ 23 ] acetaldehyde↓, γ-glutamylcysteine synthetase↑, GSH↑, GST↑, ALDH↑ Korean red ginseng ...…”
Section: Introductionmentioning
confidence: 99%
“…Black ginseng improved most of the morphological scores significantly in ethanol-treated embryos associating the significant restoration of the decreased mRNA levels of the antioxidant enzymes; cytosolic glutathione peroxidase (GPx), phospholipid hydroperoxide GPx and selenoprotein P, suggesting that black ginseng exerted this protective effect via the augmentation of antioxidative effect in the embryo [144]. Unexpectedly, in an acetaminophen-induced oxidative stress rat model, it was found that red ginseng extract exhibited more anti-oxidant activity than white ginseng and black ginseng extracts [145].…”
Section: Pharmacological Studiesmentioning
confidence: 99%
“…With these activities, KRG is therapeutically effective against various diseases [ 18 , 22 ]. Many studies have shown that KRG targets oxidative stress by inhibiting ROS formation and blocking inflammation, making it effective in various inflammatory diseases, such as atherosclerosis, coronary artery dysfunction, cancer, and neurodegenerative diseases [ [23] , [24] , [25] , [26] ]. We hypothesized that KRG could protect against the inflammation-related phenomena caused by BPA that we observed previously.…”
Section: Introductionmentioning
confidence: 99%